2020
DOI: 10.1111/jre.12836
|View full text |Cite
|
Sign up to set email alerts
|

Activated KCNQ1 channel promotes fibrogenic response in hereditary gingival fibromatosis via clustering and activation of Ras

Abstract: Background and Objective Activated potassium channels were found to be strongly correlated with gingival overgrowth (GO) phenotype as we reviewed syndromic hereditary gingival fibromatosis (HGF). Nevertheless, the functional roles of potassium channels in gingival fibrosis or gingival overgrowth remained uncovered. The aim of the present study was to explore the pathogenic role of aberrantly activated potassium channel in Hereditary Gingival Fibromatosis (HGF). Methods Gingival tissues were collected from 9 HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Previous research found that activation of the KCNQ1 potassium channel can affect the expression of fibrogenic genes and enhances the fibrotic activity of NHGFs via Ras/MAPK/AP-1 signaling. 26 ZNF513 also binds to the SOS1 promoter by ChIP-qPCR, and we found that ZNF513 ( Zfp513 ) p.R250W could increase the expression of SOS1 ( Sos1 ) in vivo, in vitro, and in mouse experiments, while the expression of SOS1 significantly decrease in ZNF513 knockout HGF cell line. SOS1 is a bifunctional guanosine monophosphate exchange factor that is down-regulated under normal physiologic condition, and its carboxyl terminal domain plays a negative regulatory role.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous research found that activation of the KCNQ1 potassium channel can affect the expression of fibrogenic genes and enhances the fibrotic activity of NHGFs via Ras/MAPK/AP-1 signaling. 26 ZNF513 also binds to the SOS1 promoter by ChIP-qPCR, and we found that ZNF513 ( Zfp513 ) p.R250W could increase the expression of SOS1 ( Sos1 ) in vivo, in vitro, and in mouse experiments, while the expression of SOS1 significantly decrease in ZNF513 knockout HGF cell line. SOS1 is a bifunctional guanosine monophosphate exchange factor that is down-regulated under normal physiologic condition, and its carboxyl terminal domain plays a negative regulatory role.…”
Section: Discussionmentioning
confidence: 78%
“…Activated Ras then promotes the activation of Raf and MEK and finally promotes the phosphorylation and nuclear translocation of ERK. 26 ZNF513 binds to the KIF3C promoter and regulates its expression. The increased expression of KIF3C regulated by mutant ZNF513 further promotes the activation of PI3K and potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Small calci ed particles, ulceration of the overlying mucosa, islands of osseous metaplasia, and in ammation can be occasionally observed [49,52]. Many studies have attempted to explore the pathogenesis of HGF currently, Gao Q et al found that KCNQ1, a member of the voltage-gated potassium channel family, played a critical role in the pathogenesis of HGF, promoted brogenic activity and facilitated extracellular matrix (ECM) synthesis and accumulation, and was upregulated in gingival tissues derived from HGF patients compared with normal gingival tissues, which may be a novel target for HGF therapy [53]. Another possible pathogenesis is the in ammatory stimulus of teeth eruption that would induce the expression of transforming growth factor ß1(TGFß1), more subepithelial broblast proliferation, greater collagen, and bronectin synthesis, reduction in the matrix metalloproteinases (MMPs), which could degrade collagen, increasing in gingival connective tissue synthesis coupled with inhibiting connective tissue decomposition [54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic variants in the disease genes KCNH1 , KCNK4 and KCNN3 all establish a significant K + conductance of the respective mutant channel in the more negative voltage range ([ 26 , 27 , 28 , 29 , 30 ], reviewed in [ 31 ]). Expression of KCNQ1 has recently been reported in human gingival fibroblasts and KCNQ1 was found to be upregulated in gingival tissue from individuals with non-syndromic hereditary gingival fibromatosis [ 32 ]. Thus, the KCNQ1 variants R116L and P369L may have a proliferative effect on gingival fibroblasts and/or cranial neural crest cells, as proposed previously [ 20 ].…”
Section: Introductionmentioning
confidence: 99%